2009
DOI: 10.1128/iai.01156-08
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regulation by theVibrio choleraeRegulator ToxT To Modulate Colonization and Anticolonization Pilus Expression

Abstract: The pathogen Vibrio cholerae uses a large number of coordinated transcriptional regulatory events to transition from its environmental reservoir to the host and establish itself at its preferred colonization site at the host intestinal mucosa. The key regulator in this process is the AraC/XylS family transcription factor, ToxT, which plays critical roles in pathogenesis, including the regulation of two type IV pili, the anticolonization factor mannose-sensitive hemagglutinin and the toxin-coregulated pilus. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
(36 reference statements)
0
26
0
1
Order By: Relevance
“…Although analogous leucine residues are not present in α3, if ToxT were to dimerize in a manner similar to that observed in AraC, complementary salt bridges would be formed between helix α3 residues such as D141, E142, K157, and K158 of one monomer and the same residues on the other monomer. In fact, Hsaio et al have suggested that a D141G substitution is able to repress msh promoters as a monomer, but is unable to activate tcp (25).…”
Section: Resultsmentioning
confidence: 99%
“…Although analogous leucine residues are not present in α3, if ToxT were to dimerize in a manner similar to that observed in AraC, complementary salt bridges would be formed between helix α3 residues such as D141, E142, K157, and K158 of one monomer and the same residues on the other monomer. In fact, Hsaio et al have suggested that a D141G substitution is able to repress msh promoters as a monomer, but is unable to activate tcp (25).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that ToxT must be dimerized to activate transcription. However, the isolated (monomeric) C terminus has been shown to bind to the mshA promoter region, which is repressed by ToxT, suggesting that monomeric ToxT, although not transcriptionally active, can still bind certain promoters and repress their expression (13).…”
mentioning
confidence: 99%
“…The P toxT -lacZ plasmid reporter was constructed by cloning toxT promoter DNA into LacZ transcriptional reporter plasmid pAH6 (30). Overnight cultures of the V. cholerae ⌬tcpPH ⌬toxRS mutant containing P toxT -lacZ reporters and various P BAD -tcpPH and P tac -toxRS plasmids were diluted 1:50 (for microaerophilic growth) or 1:2,000 (for aerobic growth) into fresh AKI medium (1.5% Bacto peptone, 0.4% yeast extract, 0.5% sodium chloride, pH 7.5) supplemented with the appropriate antibiotics, 0.01% arabinose, and 1 M IPTG and incubated at 37°C (stationary or shaking) until the OD 600 reached 0.3.…”
Section: Methodsmentioning
confidence: 99%